A STUDY ON PAKISTANI WOMEN'S PERCEPTION OF DOMESTIC VIOLENCE AND ITS ASSOCIATION WITH ANXIETY DEPRESSION AND STRESS - Dr.Fouzia Parveen; Dr. Javed Iqbal; Dr. Noor Muhammad; Qurat ul Ain Shams (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Domestic violence has been known as a most serious matter facing Pakistani women. The key objective of the existing study was to look at the experiences of domestic violence in the opinion of survivor females and its association with stress, depression and anxiety in Pakistani females. The sample was 58 women, whose age range 15 to 49, were chosen from the Dar-ul-Falah (shelter homes from government) in the Punjab cities of Lahore, Sargodha, Rawalpindi, Sialkot, Multan, and Bahawalpur in Pakistan. This was a mixed method survey study. First stage of data collection was the selection of a tool (DASS 21) Depression, Anxiety and Stress Scale was adapted. In qualitative study, in depth interviews also conducted by the researcher to examine the women’s experiences and understanding about domestic violence and its association with stress, depression and anxiety due to domestic violence. The information according to the circumstance on the source of interviews and prior history that was available in Dar-ul-Falah’s records and files exhibited that domestic abuse had a positive association with anxiety, stress and depression and results showed that socioeconomic factors and family played a significant role in frustrating of domestic violence and psychological problems linked by the survivors were sleep problems, post-traumatic, stress disorder, feelings of hopelessness, low self-esteem, depression, helplessness, and weak self-concept. As per the conclusions from this research, domestic violence is very harmful for victims. Women experience stress, anxiety, depression and other psychological issues. Results from the current study suggested that domestic violence can be reduced by giving positive training to young men and implementation of Anti domestic violence departments.